ANALISIS PERBANDINGAN PENERIMAAN PAJAK DAERAH SEBELUM DAN SELAMA PANDEMI COVID-19 SE-SUMATRA - Al Wafa, Imtiyaz; Masnila, Nelly; Antina Aryanti, Yuli (Jurnal Manajemen & Bisnis Jayakarta, 2023)
The Covid-19 a pandemic emerged in late 2019 and has spread across the world, including Indonesia. The first case occurred in March 2020, resulting in a downturn in the economy and a decline in tax revenues in affected areas. The purpose of this study is to analyze the regional tax revenue comparison of various regions/cities in Sumatra, taking regions/cities as research samples. This study used a statistical test tool, the paired-samples t-test of SPSS application version 26. Such studies are comparative quantitative studies, using only samples from different treatments of the same study, i.e. before and during Covid -19 disease, compared to the epidemic. Using the target sample, the total population for the period 2018-2021 is 154 population, consisting of 11 local taxes, so the sample used is only 35 districts/cities in Sumatra. The results of this study indicate that there are differences in Regional Tax revenue before and during the Covid-19 Pandemic with details of 9 (nine) taxes affected and 2 (two) others not affected by the Covid-19 pandemic.